Cavity closure of 2-hydroxypropyl-β-cyclodextrin: Replica exchange molecular dynamics simulations - Khanittha Kerdpol (2019)
© 2019 by the authors. 2-Hydroxypropyl-β-cyclodextrin (HPβCD) has unique properties to enhance the stability and the solubility of low water-soluble compounds by inclusion complexation. An understanding of the structural properties of HPβCD and its derivatives, based on the number of 2-hydroxypropyl (HP) substituents at the α-D-glucopyranose subunits is rather important. In this work, replica exchange molecular dynamics simulations were performed to investigate the conformational changes of singleand double-sided HP-substitution, called 6-HPβCDs and 2,6-HPβCDs, respectively. The results show that the glucose subunits in both 6-HPβCDs and 2,6-HPβCDs have a lower chance of flipping than in βCD. Also, HP groups occasionally block the hydrophobic cavity of HPβCDs, thus hindering drug inclusion. We found that HPβCDs with a high number of HP-substitutions are more likely to be blocked, while HPβCDs with double-sided HP-substitutions have an even higher probability of being blocked. Overall, 6-HPβCDs with three and four HP-substitutions are highlighted as the most suitable structures for guest encapsulation, based on our conformational analyses, such as structural distortion, the radius of gyration, circularity, and cavity self-closure of the HPβCDs.